Analysis of supercritical heat transfer in horizontal helical tube with internal roughness. (5th July 2022) - Jiang, Yi-Ran; Hu, Peng; Jia, Cheng-Qi; Zhao, Pan-Pan; Jia, Lei
Highlights: Supercritical flow in horizontal helical tube with internal roughness is analyzed. Circumferential non-uniformity and axial oscillation of Tw are explored. The internally ribbed roughness and concaved roughness are compared. The effects of spiral roughness, centrifugal force, and buoyancy are revealed. Abstract: Helically coiled tube with smooth wall (HSW) has been widely used in the fields of supercritical air conditioning systems and supercritical heat pump systems due to its compact structure and excellent heat transfer performance. However, its large circumferential non-uniformity and intense axial oscillation will bring to local stress concentration and instability of heat transfer which are both responsible for system accidents. To alleviate the above two crises, the spiral inner wall roughness is proposed to be introduced into HSW. Up to now, the performance of helically coiled tube with internally ribbed roughness (HRW) has been seldom reported and the effectivenesses of inner roughness with different structures on suppressing circumferential non-uniformity and axial oscillation are still unclear. In this work, the SST k - ω model is employed to simulate the turbulent flow of s-R1234ze(E) in horizontal HRW to fill these gaps. Firstly, the effectivenesses of different rib heights, rib lift angles, rib widths, rib numbers, and rib base angles on restraining circumferential non-uniformity and axial oscillation are explored. The influences of wall thickness are also contained. Subsequently, the internally ribbed roughness and concaved roughness are compared and evaluated according to the overall comprehensive performance criterion. Finally, the effects of spiral roughness, centrifugal force, and gravitational buoyancy force on the flow field distributions are also revealed.